Developing and evaluating a course programme to enhance existential communication with cancer patients in general practice. (3rd April 2018) - Hvidt, Elisabeth Assing; Ammentorp, Jette; Søndergaard, Jens; Timmermann, Connie; Hansen, Dorte Gilså; Hvidt, Niels Christian
Abstract: Objective: Our objective was to describe the development and evaluation of a course programme in existential communication targeting general practitioners (GPs). Design: The UK Medical Research Council's (MRC) framework for complex intervention research was used as a guide for course development and evaluation and was furthermore used to structure this paper. The development phase included: identification of existing evidence, description of the theoretical framework of the course, designing the intervention and deciding for types of evaluation. In the evaluation phase we measured self-efficacy before and after course participation. To explore further processes of change we conducted individual, semi-structured telephone interviews with participants. Subjects and setting: Twenty practising GPs and residentials in training to become GPs from one Danish region (mean age 49). Results: The development phase resulted in a one-day vocational training/continuing medical education (VT/CME) course including the main elements of knowledge building, self-reflection and communication training. Twenty GPs participated in the testing of the course, nineteen GPs answered questionnaires measuring self-efficacy, and fifteen GPs were interviewed. The mean scores of self-efficacy increased significantly. The qualitative results pointed to positive post course changes such as an increase in the participants' existential self-awareness, an increase in awareness of patients in need of existential communication, and an increase in the participants' confidence in the ability to carry out existential communication. Conclusions: A one-day VT/CME course targeting GPs and including the main elements of knowledge building, self-reflection and communication training showed to make participants more confident about their ability to communicate with patients about existential issues and concerns. Key points: Patients with cancer often desire to discuss existential concerns as part of clinical care but general practitioners (GPs) lack confidence when discussing existential issues in daily practice. In order to lessen barriers and enhance existential communication in general practice, we developed a one-day course programme. Attending the course resulted in an increase in the participants' confidence in the ability to carry out existential communication. This study adds knowledge to how confidence in existential communication can be increased among GPs.